The concept of scarcity: An Islamic perspective - Fontaine, Rodrigue Ancelot Harvey; Oziev, Gapur (Malaysian Institute of Management, 2013)
This article was published in the Malaysian Management Review (MMR) (Vol 48, No 1) in 2013. The MMR is the official journal of the Malaysian Institute of Management. It deals with Scarcity from an Islamic perspective. Scarcity has been a subject of contention among Muslim scholars. Whereas the concept is central to conventional economics in relation to choice and efficiency, Muslim scholars differ about it. The purpose of this study is to summarize the differences of opinion and provide a conclusion to this issue. We hypothesise that the difference in the educational backgrounds of Muslim scholars partially explains their diverse opinions on scarcity. Some scholars have a strong background in economics whereas other scholars have a strong background in Islamic law (Shari’ah). Some scholars reject outright the existence of scarcity and believe in abundant resources while others confirm the presence of scarcity. Other scholars believe there is no scarcity at the macro-level but that can be scarcity at the micro-level. Although the Qur’an provides ample evidence of God’s generosity and mercy in providing to humankind, it is still necessary to consider our daily needs and wants, which vary from society to society and from generation to generation. On the contrary, the Qur’an provides evidence that facing scarcity is part of God’s way of testing His creatures.